Method for microwave-assisted construction of high-elastic three-dimensional network structure of potassium feldspar geopolymer

CN118479819BActive Publication Date: 2026-10-30GUANGXI UNIVERSITY OF TECHNOLOGY
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410576342.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-05-10
Publication Date
2026-10-30
Estimated Expiration
2044-05-10

AI Technical Summary

Technical Problem

此外,由于脆性破坏缺乏显著的弹性变形,一旦出现脆性破坏,破坏会迅速扩散,可能导致结构的突然坍塌

Benefits of technology

[0022]1、本发明首先将纤维在水中经过长时间的浸泡,使纤维骨架上的羟基能够充分吸附大量水分子,随后通过充分的搅拌,带有大量水分子的纤维可以均匀分布在混凝土基体中,当混凝土基体接受微波处理时,整个混凝土基体均存在分子运动,从而能够形成完美的高弹三维网络结构。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118479819B_ABST
    Figure CN118479819B_ABST
Patent Text Reader

Abstract

The present application relates to the field of geopolymer preparation, and particularly relates to a method for microwave-assisted construction of high-elastic three-dimensional network structure of potassium feldspar geopolymer, comprising the following steps: (1) taking fibers, soaking the fibers in water to obtain swollen fibers; (2) taking potassium feldspar waste and cement, stirring and uniformly mixing to obtain dry material A; (3) taking additives and water, stirring and uniformly mixing to obtain solution B; (4) stirring and uniformly mixing dry material A and solution B, then adding the swollen fibers obtained in step (1), stirring and uniformly mixing to obtain geopolymer slurry; (5) pouring the geopolymer slurry into a mold for casting and curing to obtain a test block, then taking the test block out of the mold and placing it into a microwave reactor for microwave treatment, and obtaining the high-elastic three-dimensional network structure of potassium feldspar geopolymer through microwave-assisted construction. The potassium feldspar geopolymer prepared by the method has high-elastic three-dimensional network structure, high compressive strength and high elastic modulus, and will not be broken in brittleness when facing external impact and pressure.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of geopolymer preparation, and in particular to a method for microwave-assisted construction of a highly elastic three-dimensional network structure of potassium feldspar geopolymer. Background Technology

[0002] Because potassium feldspar waste contains components that can form geopolymers, we use potassium feldspar waste in geopolymer production to reduce the accumulation of these wastes and thus alleviate the pressure on the environment.

[0003] However, potassium feldspar polymer specimens cannot form a good, highly elastic three-dimensional network structure during traditional curing processes, leading to brittle failure when faced with external impacts and pressures. This contradicts the goal of elastic failure sought in engineering, as this type of failure often occurs without any significant deformation or cracking, resulting in almost no effective early warning signal before structural failure. This contrasts sharply with elastic failure, which is usually accompanied by significant deformation and cracking, providing engineers with time to take countermeasures. Furthermore, because brittle failure lacks significant elastic deformation, once it occurs, the damage spreads rapidly, potentially leading to a sudden collapse of the structure. Such instantaneous collapse can not only cause casualties but also significant property damage, especially in critical structural applications such as bridges and high-rise buildings, where the consequences are particularly severe.

[0004] Therefore, it is necessary to seek a microwave-assisted technique for constructing a highly elastic three-dimensional network structure of potassium feldspar geopolymers to improve the elasticity of potassium feldspar geopolymers. Summary of the Invention

[0005] The purpose of this invention is to provide a method for constructing a highly elastic three-dimensional network structure of potassium feldspar geopolymer using microwave assistance, which addresses the aforementioned problems. The potassium feldspar polymer prepared by this method has high elastic modulus and compressive strength.

[0006] To achieve the above objectives, the present invention adopts the following technical solution: 1. A method for microwave-assisted construction of a potassium feldspar geopolymer high-elasticity three-dimensional network structure, comprising the following steps:

[0007] (1) Take the fiber and soak it in water to obtain swollen fiber;

[0008] (2) Take potassium feldspar waste and cement, mix them thoroughly to obtain dry material A;

[0009] (3) Take the additive and water, stir and mix well to obtain solution B;

[0010] (4) After mixing dry material A and solution B, add the swollen fiber obtained in step (1) and stir evenly to obtain geopolymer slurry;

[0011] (5) The geopolymer slurry is poured into a mold and solidified by static curing to obtain a test block. The test block is demolded and placed in a microwave reactor for microwave treatment. A potassium feldspar geopolymer high elastic three-dimensional network structure is obtained by microwave-assisted construction.

[0012] Furthermore, the mass ratio of the raw materials used is: potassium feldspar waste: cement: fiber: admixture: water = 2~5: 1: 0.1~0.4: 0.05~0.35: 1.2~2.

[0013] Furthermore, the fiber described in step (1) is soaked in water for 18h to 36h.

[0014] Furthermore, the fiber is one or more of PVA fiber, kapok fiber, glass fiber, jute fiber, and oil palm fiber.

[0015] Furthermore, the potassium feldspar waste has a particle size of <400μm.

[0016] Furthermore, the cement is one or more of silicate cement, calcium aluminate cement, sulfoaluminate cement, and fly ash silicate cement.

[0017] Furthermore, the additive is composed of calcium sulfate, quicklime, and sodium aluminate mixed in a mass ratio of 2:2:1.

[0018] Furthermore, in step (5), the microwave power is 100-800W and the microwave irradiation time is 10-60min.

[0019] Furthermore, the curing time in step (5) is one day.

[0020] In addition, the present invention also provides a potassium feldspar geopolymer prepared by the above method.

[0021] In summary, due to the adoption of the above technical solution, the present invention has the following beneficial effects:

[0022] 1. The present invention first soaks the fiber in water for a long time, so that the hydroxyl groups on the fiber skeleton can fully adsorb a large number of water molecules. Then, through thorough stirring, the fiber with a large number of water molecules can be evenly distributed in the concrete matrix. When the concrete matrix is ​​subjected to microwave treatment, molecular movement occurs throughout the entire concrete matrix, thereby forming a perfect high-elasticity three-dimensional network structure.

[0023] 2. This invention utilizes microwave-assisted construction to obtain a highly elastic three-dimensional network structure of potassium feldspar geopolymer. Microwave treatment, with its internal heating characteristics, causes water molecules adsorbed on the fiber skeleton to vibrate. During this vibration, the high-speed molecular motion significantly enhances the contact frequency between water molecules and active particles, promoting their interaction and accelerating the hydration reaction. This process not only promotes the construction of the structural morphology but also gradually forms a highly elastic three-dimensional network structure of potassium feldspar geopolymer over time. This invention controls the construction of the three-dimensional network structure of potassium feldspar geopolymer by changing the fiber soaking time, microwave power, and microwave time, resulting in potassium feldspar concrete specimens with high elastic modulus. Mechanical property testing of the potassium feldspar geopolymer specimens prepared using the method provided by this invention shows that their compressive strength is greater than 35 MPa and their elastic modulus is greater than 32 GPa. These high compressive strength and elastic modulus prevent brittle fracture when faced with external impacts and pressures, providing engineers with time to take countermeasures and potentially reducing casualties and property damage.

[0024] 3. This invention uses microwave-assisted preparation of potassium feldspar geopolymers, eliminating the need for complex organic solvents or other hazardous chemicals. The entire process is green and safe, meeting environmental protection requirements. Furthermore, the convenience of microwave heating simplifies the entire process, making the equipment easy to operate and maintain, and highly suitable for large-scale industrial production. Attached Figure Description

[0025] Figure 1 This is a scanning electron microscope image of the high-elasticity three-dimensional network structure of potassium feldspar geopolymer prepared in Example 1.

[0026] Figure 2 This is a scanning electron microscope image of the high-elasticity three-dimensional network structure of potassium feldspar geopolymer prepared in Example 2.

[0027] Figure 3 This is a scanning electron microscope image of the high-elasticity three-dimensional network structure of potassium feldspar geopolymer prepared in Example 3.

[0028] Figure 4 The image shows a scanning electron microscope (SEM) image of the high-elasticity three-dimensional network structure of potassium feldspar geopolymer prepared in Comparative Example 1.

[0029] Figure 5 The image shows a scanning electron microscope (SEM) image of the high-elasticity three-dimensional network structure of potassium feldspar geopolymer prepared in Comparative Example 2. Detailed Implementation

[0030] This embodiment provides a method for microwave-assisted construction of a potassium feldspar geopolymer high-elasticity three-dimensional network structure, including the following steps:

[0031] (1) Take the fiber and soak it in water for 18h to 36h to obtain swollen fiber; wherein the fiber is one or more of PVA fiber, kapok fiber, glass fiber, jute fiber and oil palm fiber;

[0032] (2) Take potassium feldspar waste with a particle size <400μm and cement, stir and mix them to obtain dry material A; wherein the cement is one or more of silicate cement, calcium aluminate cement, sulfoaluminate cement and fly ash silicate cement.

[0033] (3) Take the additive made of calcium sulfate, quicklime and sodium aluminate in a mass ratio of 2:2:1 and water, stir and mix well to obtain solution B;

[0034] The mass ratio of the raw materials used in steps (1) to (3) is: potassium feldspar waste: cement: fiber: admixture: water = 2-5: 1: 0.1-0.8: 0.05-1: 1.2-2.3;

[0035] (4) After mixing dry material A and solution B, add the swollen fiber obtained in step (1) and stir evenly to obtain geopolymer slurry;

[0036] (5) The geopolymer slurry is poured into a mold and solidified for one day to obtain a test block. The test block is demolded and placed in a microwave reactor for microwave treatment. The microwave power is 100-800W and the microwave irradiation time is 10-60min. A potassium feldspar geopolymer is obtained by microwave-assisted construction. The potassium feldspar geopolymer has a highly elastic three-dimensional network structure.

[0037] To more clearly illustrate the present invention, the following specific embodiments will be used to further explain the invention.

[0038] Example 1

[0039] Construct a potassium feldspar geopolymer high-elasticity three-dimensional network structure according to the following steps:

[0040] (1) Take 50.6g of PVA fiber and soak the PVA fiber in water for 18h to obtain swollen PVA fiber;

[0041] (2) Take 1011.5g of potassium feldspar waste and 505.7g of silicate cement, stir and mix them to obtain dry material A;

[0042] (3) Take 10.1g of calcium sulfate, 10.1g of quicklime, 5.1g of sodium aluminate and 606.9g of water, stir and mix well to obtain solution B;

[0043] (4) After mixing dry material A and solution B, add the swollen PVA fiber obtained in step (1) and stir at high speed until uniform to obtain geopolymer slurry.

[0044] (5) After the geopolymer slurry is poured into the mold and allowed to stand and solidify for one day, the mold is removed to obtain the test block. The test block is placed in the microwave reactor, the microwave power is set to 100W and the microwave time is 60min. Then the microwave reactor is started to microwave the sample and microwave treatment is performed. Microwave-assisted construction of a high-elasticity three-dimensional network structure of potassium feldspar geopolymer is started. A potassium feldspar geopolymer with a high-elasticity three-dimensional network structure is obtained through microwave-assisted construction.

[0045] Example 2

[0046] Construct a potassium feldspar geopolymer high-elasticity three-dimensional network structure according to the following steps:

[0047] (1) Take 84g of kapok fiber and soak the kapok fiber in water for 27h to obtain swollen kapok fiber;

[0048] (2) Take 1175.6g of potassium feldspar waste and 335.9g of aluminate cement, stir and mix them to obtain dry material A;

[0049] (3) Take 26.9g of calcium sulfate, 26.9g of quicklime, 13.4g of sodium aluminate and 537.4g of water, stir and mix well to obtain solution B;

[0050] (4) After mixing dry material A and solution B, add the swollen kapok fiber obtained in step (1) and stir at high speed until uniform to obtain geopolymer slurry.

[0051] (5) After the geopolymer slurry is poured into the mold and allowed to stand and solidify for one day, the mold is removed to obtain the test block. The test block is placed in the microwave reactor, the microwave power is set to 400W and the microwave time is 30min. Then the microwave reactor is started to microwave the sample and microwave treatment is performed. Microwave-assisted construction of potassium feldspar geopolymer high elastic three-dimensional network structure is started. A potassium feldspar geopolymer with high elastic three-dimensional network structure is obtained through microwave-assisted construction.

[0052] Example 3

[0053] Construct a potassium feldspar geopolymer high-elasticity three-dimensional network structure according to the following steps:

[0054] (1) Take 100.6g of glass fiber and soak it in water for 36 hours to obtain swollen glass fiber;

[0055] (2) Take 1257.1g of potassium feldspar waste and 251.4g of sulfoaluminate cement, stir and mix them to obtain dry material A;

[0056] (3) Take 35.2g of calcium sulfate, 35.2g of quicklime, 17.6g of sodium aluminate and 502.9g of water, stir and mix well to obtain solution B;

[0057] (4) After mixing dry material A and solution B, add the swollen glass fiber obtained in step (1) and stir at high speed until uniform to obtain geopolymer slurry.

[0058] (5) After the geopolymer slurry is poured into the mold and allowed to stand and solidify for one day, the mold is removed to obtain the test block. The test block is placed in the microwave reactor, the microwave power is set to 800W and the microwave time is 10min. Then the microwave reactor is started to microwave the sample and microwave treatment is performed. Microwave-assisted construction of potassium feldspar geopolymer high elastic three-dimensional network structure is started. A potassium feldspar geopolymer with high elastic three-dimensional network structure is obtained through microwave-assisted construction.

[0059] Comparative Example 1

[0060] Construct a potassium feldspar geopolymer high-elasticity three-dimensional network structure according to the following steps:

[0061] (1) Take 50.6g of PVA fiber and soak the fiber in water for 18h to obtain swollen PVA fiber;

[0062] (2) Take 1011.5g of potassium feldspar waste and 505.7g of silicate cement, stir and mix them to obtain dry material A;

[0063] (3) Take 10.1g of calcium sulfate, 10.1g of quicklime, 5.1g of sodium aluminate and 606.9g of water, stir and mix well to obtain solution B;

[0064] (4) After mixing dry material A and solution B, add the swollen PVA fiber obtained in step (1) and stir at high speed until uniform to obtain geopolymer slurry.

[0065] (5) The geopolymer slurry was poured into the mold and solidified for one day. The mold was then removed to obtain a test block, which was placed in a curing box for 28 days to obtain a potassium feldspar geopolymer high elastic three-dimensional network structure.

[0066] Comparative Example 2

[0067] Construct a potassium feldspar geopolymer high-elasticity three-dimensional network structure according to the following steps:

[0068] (1) Take 1011.5g of potassium feldspar waste, 505.7g of silicate cement and 50.6g of PVA fiber, stir and mix them to obtain dry material A.

[0069] (2) Take 10.1g of calcium sulfate, 10.1g of quicklime, 5.1g of sodium aluminate and 606.9g of water, stir and mix well to obtain solution B;

[0070] (3) Mix dry material A and solution B to obtain geopolymer slurry.

[0071] (4) After the geopolymer slurry is poured into the mold and allowed to stand and solidify for one day, the mold is removed to obtain the test block. The test block is placed in the microwave reactor, the microwave power is set to 100W and the microwave time is 60min. Then the microwave reactor is started to microwave the sample and microwave-assisted construction of potassium feldspar geopolymer high elastic three-dimensional network structure is started. A potassium feldspar geopolymer high elastic three-dimensional network structure is obtained through microwave-assisted construction.

[0072] The raw materials used in Examples 1-3 of this application and the performance test results of the prepared geopolymers are shown in Table 1, and their scanning electron microscope images are shown below. Figure 1-3 As shown in the figure; the raw materials used in Example 1 and Comparative Examples 1-2 and the performance test results of the prepared geopolymers are shown in Table 2, and their scanning electron microscope images are shown in the figure. Figure 4-5 As shown;

[0073] Table 1. Test results of raw materials and geopolymers used in Examples 1-3.

[0074]

[0075]

[0076] Table 2. Test results of raw materials and geopolymers used in Examples 1 and 1-2.

[0077]

[0078] As shown in Table 1, the potassium feldspar geopolymer samples prepared in Examples 1-3, after mechanical property testing, exhibited a compressive strength greater than 35 MPa and an elastic modulus greater than 32 GPa. This is because the present invention first soaks the fibers in water for an extended period, allowing the hydroxyl groups on the fiber skeleton to fully adsorb a large number of water molecules. Microwave curing rapidly increases the internal temperature of the geopolymer, enabling the active particles to fully react with the water molecules. This process not only promotes the construction of the structural morphology but also gradually forms a highly elastic three-dimensional network structure of the potassium feldspar geopolymer over time. Consequently, the prepared potassium feldspar geopolymer possesses high compressive strength and elastic modulus, preventing brittle fracture under external impact and pressure. This provides engineers with time to take countermeasures, reducing casualties and property damage to a certain extent.

[0079] As shown in Table 2, the performance of the potassium feldspar geopolymer specimens prepared in Comparative Examples 1 and 2 was reduced compared to Example 1. Specifically, Comparative Example 1 did not microwave-treat the potassium feldspar geopolymer specimens, preventing water molecules in the concrete from moving at high speeds, thus affecting the construction of the high-elasticity three-dimensional network structure within the potassium feldspar geopolymer. Comparative Example 2 did not soak the fibers in water, resulting in insufficient water molecules in the concrete to vibrate during the construction of the high-elasticity three-dimensional network structure of the potassium feldspar geopolymer, thereby affecting the elasticity of the internal three-dimensional network structure of the potassium feldspar geopolymer.

[0080] The above description is a detailed description of the preferred embodiments of the present invention. However, the embodiments are not intended to limit the scope of the patent application of the present invention. All equivalent changes or modifications made under the technical spirit of the present invention should fall within the patent scope covered by the present invention.

Claims

1. A method for microwave-assisted construction of a highly elastic three-dimensional network structure of potassium feldspar geopolymer, characterized in that, Includes the following steps: (1) Take the fiber and soak it in water to obtain swollen fiber; (2) Take potassium feldspar waste and cement, mix them thoroughly to obtain dry material A; (3) Take the additive and water, stir and mix well to obtain solution B; (4) After mixing dry material A and solution B, add the swollen fiber obtained in step (1), stir evenly, and obtain geopolymer slurry; (5) The geopolymer slurry is poured into a mold and solidified by static curing to obtain a test block. The test block is demolded and placed in a microwave reactor for microwave treatment. A potassium feldspar geopolymer high elastic three-dimensional network structure is obtained by microwave-assisted construction. The mass ratio of the raw materials used is as follows: potassium feldspar waste: cement: fiber: admixture: water = 2~5:1:0.1~0.4:0.05~0.35:1.2~2; the fiber in step (1) is soaked in water for 18h~36h; the fiber is one or more of PVA fiber, kapok fiber, glass fiber, jute fiber, and oil palm fiber; the admixture is a mixture of calcium sulfate, quicklime, and sodium aluminate in a mass ratio of 2:2:1; the microwave power in step (5) is 100~800W, and the microwave irradiation time is 10~60min.

2. The method for constructing a microwave-assisted, high-elasticity three-dimensional network structure of potassium feldspar geopolymer according to claim 1, characterized in that, The potassium feldspar waste has a particle size of <400μm.

3. The method for constructing a microwave-assisted, high-elasticity three-dimensional network structure of potassium feldspar geopolymer according to claim 1, characterized in that, The cement is one or more of silicate cement, calcium aluminate cement, sulfoaluminate cement, and fly ash silicate cement.

4. The method for microwave-assisted construction of a potassium feldspar geopolymer high-elasticity three-dimensional network structure according to claim 1, characterized in that, The curing time in step (5) is one day.

5. A potassium feldspar geopolymer prepared by the method according to any one of claims 1-4.

Citation Information

Patent Citations

  • Geopolymer material, adaptive retarder and prepared high-temperature resistant well cementation cement paste

    CN110092597A

  • Method for solidifying lead alkali residues by using fly ash-based geopolymer with assistance of microwaves

    CN110981302A